Numerical simulation of forced convective fish drying performance of different cabinet geometry - Joshua Kolawole Gbegudu; Ibrahim Ademola Fetuga; Olabode Thomas Olakoyejo; Manasseh Babale Shitta; Antonio Marcos de Oliveira Siqueira; Emmanuel Obiani Akari; Kolade Sodeeq Aderemi (The Journal of Engineering and Exact Sciences)
Two forced convective fish rotary dryers of different geometries (cube and cylindrical) with modelled fish were simulated using ANSYS commercial software to determine the geometry that gives an optimal inlet temperature distribution profile, which ultimately leads to faster drying of fish. The geometries were constructed using CATIA V5 modelling software such that they both have the same volume, so they can be compared appropriately. The simulation was carried out for different inlet temperatures and at different time intervals. From the simulations carried out, it was discovered that the cylindrical rotary dryer possesses the maximum mean dryer temperatures in most of the time intervals considered. The temperature distribution obtained thus reveals that the cylindrical d duration of thermal action on the products. Therefore, the cylindrical rotary dryer gives an increased drying rate and an improved quality of product.